2005
DOI: 10.1007/s00439-005-1271-6
|View full text |Cite
|
Sign up to set email alerts
|

Different population histories of the Mundari- and Mon-Khmer-speaking Austro-Asiatic tribes inferred from the mtDNA 9-bp deletion/insertion polymorphism in Indian populations

Abstract: Length variation in the human mtDNA intergenic region between the cytochrome oxidase II (COII) and tRNA lysine (tRNA(lys)) genes has been widely studied in world populations. Specifically, Austronesian populations of the Pacific and Austro-Asiatic populations of southeast Asia most frequently carry the 9-bp deletion in that region implying their shared common ancestry in haplogroup B. Furthermore, multiple independent origins of the 9-bp deletion at the background of other mtDNA haplogroups has been shown in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 43 publications
4
29
3
Order By: Relevance
“…But this is not the case in reality and thus goes against the view point of Kayser et al (2003) on Austro-Asiatic migration from Southeast Asia to India. However mtDNA markers show a different picture of migration as suggested by Kumar et al (2006) and Thangaraj et al (2005). The foundation of M31 and M32 macrohaplogroup of mt DNA in India along with its migration shows some new insight like recent gene flow from Northeast India to Southeast Asia (Barik et al 2009, Wang et al 2011.…”
Section: Origin and Spread Of Hemoglobin Ementioning
confidence: 99%
“…But this is not the case in reality and thus goes against the view point of Kayser et al (2003) on Austro-Asiatic migration from Southeast Asia to India. However mtDNA markers show a different picture of migration as suggested by Kumar et al (2006) and Thangaraj et al (2005). The foundation of M31 and M32 macrohaplogroup of mt DNA in India along with its migration shows some new insight like recent gene flow from Northeast India to Southeast Asia (Barik et al 2009, Wang et al 2011.…”
Section: Origin and Spread Of Hemoglobin Ementioning
confidence: 99%
“…Presence of an Austro-Asiatic speaking tribe, Khasi, among the Tibeto-Burman speaking neighbors in the northeast corroborates this assumption. While the Tibeto-Burman speakers brought in a number of East Asian maternal lineages (A, B5b, F1b, M8c, M8z) (Metspalu et al 2004), absence of these lineages in AustroAsiatic tribes (Thangaraj et al 2005;Sahoo 2006a) portrays two different scenarios. First, the earlier exodus from South East Asia was probably a major male-mediated migration into India, or that the female gene pool of the migrating East Asians is completely lost among the Austro-Asiatic tribes.…”
Section: Insights Into Origin Of Austro-asiatic and Tibeto-burman Spementioning
confidence: 99%
“…Their maternal lineages, on the other hand, are diverse but largely Indian, consisting of M*, M3a, M5, M5b, M6, M30, and R6, and completely lacking East Eurasian-specific mitochondrial haplogroups such as A, F2, D4, M7, M8, and 9-bp deletions (Roychoudhary et al, 2001;Metspalu et al, 2004;Thangaraj et al, 2005a; present study). Recently, Thangaraj et al (2005a) reported the presence of a few Southeast Asian-specific mtDNA haplogroups (B4 and B5a) in mainland Indo-European and Dravidian populations, but none of these haplogroups were found among the 302 Mundari-speakers analyzed in the study. This provides clear evidence that founders of the male gene pool of Austro-Asiatic tribes of India probably belonged to Southeast Asia, while their female counterparts exclusively harbor Indian-specific maternal lineages.…”
Section: Discussionmentioning
confidence: 52%
“…The O2a Y-chromosome haplogroup contributed to almost 60% of their paternal gene pool, indicating a common paternal ancestry, probably among the Austro-Asiatic speakers of South China, the place of geographic origin for O2a (Karafet et al, 2001). Their maternal lineages, on the other hand, are diverse but largely Indian, consisting of M*, M3a, M5, M5b, M6, M30, and R6, and completely lacking East Eurasian-specific mitochondrial haplogroups such as A, F2, D4, M7, M8, and 9-bp deletions (Roychoudhary et al, 2001;Metspalu et al, 2004;Thangaraj et al, 2005a; present study). Recently, Thangaraj et al (2005a) reported the presence of a few Southeast Asian-specific mtDNA haplogroups (B4 and B5a) in mainland Indo-European and Dravidian populations, but none of these haplogroups were found among the 302 Mundari-speakers analyzed in the study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation